Comparison of the Effectiveness of Yoga and Psychotherapy group Therapy Based on Acceptance and Commitment on Fatigue and Quality of Life of Multiple Sclerosis Patients - Raheleh Rezaeian Langroodi; Masoud Ghiasian; Mehdi Roozbehani; Farshid Shamsaei (Hamadan University of Medical Sciences, 2020)
Introduction: Multiple sclerosis (MS) is a chronic and debilitating disease of the central nervous system. Chronic illness and lack of definitive treatment reduce all aspects of physical and social functioning and thus reduce quality of life. The aim of this study was to compare the effectiveness of a group of yoga and psychotherapy group exercises based on acceptance and commitment to fatigue and quality of life of patients with MS. Methods: In the present quasi-experimental study (pre-test-post-test design), 60 women with MS referred to the Neshat Clinic in Hamadan were selected randomly, considering entry criteria and then divided into two equal groups of yoga exercises and acceptance and commitment-based therapy groups (both 12 sessions each). Data were analyzed using independent t-test, Chi-score and Fisher's exact test, analysis of covariance and LSD with 95% confidence level by SPSS software version 22. Results: The results showed that compared to group psychotherapy based on acceptance and commitment, yoga group demonstrated -5.29±0.69 units of reduction in the fatigue score and 8.39±1.11 units of decrease in quality of life score which was statistically significant (P <0.001). Conclusion: It can be concluded that yoga and group psychotherapy based on acceptance and commitment reduce fatigue and increase the quality of life of patients with MS. It is effective that these results can promise a new development in interventions, so that in addition to drug treatment, complementary therapies can be used to reduce the complications of the disease.